Physical, chemical and nutritional characterization of de-greased corn germ - Granito, Marisela; Guerra, Marisa; Torres, Alexia (Rev. Téc. Fac. Ing. Univ. Zulia)
Corn is separated into endosperm and germ by industrial processing, and oil extraction of the later gives defatted corn germ (DCG) as a by-product. After grounding the DCG, three fractions are obtained which differ in particle size: a fine fraction (FF), commercialized for human consumption; a medium fraction (MF) and a coarse fraction (CF), commercialized for animal consumption. The purpose of this study was the physical, chemical and nutritional characterization of fractions FF and MF, in order to determine their proximal composition, water retention capacity, minerals, aminoacid content and protein quality. This knowledge would allow us the recommendation and possible use of DCG as a source of nutrients and/or as partial substitute of wheat flour (WF) for food development. It was determined that FF and MF contain 13% of good quality protein (PER = 68.41% FF and 66.58% MF, with respect to casein/cellulose PER) and a total dietary fiber content of 24% and 36%, respectively. When compared to WF, both fractions have relatively higher concentrations of almost all the aminoacids and higher concentrations of potassium, magnesium, phosphorous, calcium and iron. The fact that the DCG fractions are rich in nutrients and dietary fiber allows us to suggest their use as food supplements for massive consumption.